The Future Of Female Leadership In Education: Challenges And Opportunities - Khanal, Nabin (Jana Adarsha Research Journal, 2025)
Though female surpass men both in quantity and quality in academic world as a whole, many of them evade themselves from workforce participation because of various causes. Further, those who are in workforce are very rare in top roles and are massively in subsidiary roles. In addition, women have to overcome a variety of hurdles when in leadership roles and being an aspirant for it. Based on the above background, this review was started aiming to access the challenges women face ascending the leadership positions. The gap in leadership roles and the future prospects of women to occupy the roles made this study a necessity. Two major academic and scientific journals as ResearchGate and Google Scholar have been selected. Twenty different review articles were selected for analysis and thematized into five heads namely female in politics, female in education, need of female leaders in education, barriers and biases to female leadership and strengthening female leadership through inclusion. Even though women are doing well in education and politics, developing networking and leadership skills, they are still blocked to achieve leadership roles. Persistent barriers exist for women to achieve the position which ranges from personal, organizational, and cultural as well. These insights have implications for the future personnel management especially in leadership positions in the educational institutions in the scenario of teaching being the job of less attraction for males.